Every breath you take - Clark, Mary Higgins; Burke, Alafair (Clark, Mary Higgins. Under suspicion novel., 2017)
The Met Gala ball: the world<U+2019>s most glamorous fundraising party, an incredible night where the rich and famous wear extraordinary designer gowns and rub shoulders in New York<U+2019>s famous Metropolitan Museum of Art. People would kill for an invitation. Three years ago, Virginia Wakeling, a member of the Met<U+2019>s board of trustees and one of the museum<U+2019>s most generous donors, was found dead in the snow outside the building. Police soon discovered that she<U+2019>d been thrown from the roof during the Met Gala, but no one has ever been arrested for her murder. Although suspicion has always hovered around Virginia<U+2019>s much younger boyfriend, there are a bevy of suspects. Laurie Moran decides to investigate Virginia<U+2019>s death for her successful cold-cases television show, Under Suspicion. But the more she pries into Virginia<U+2019>s murder, the closer Laurie comes to discovering just how dangerous an invitation to the Met Gala can be<U+2026>